IMPROVING THE VOCABULARY SKILLS OF FOOD TECHNOLOGY STUDENTS THROUGH PROJECT-RESEARCH ACTIVITIES - Djabbarova Dilfuza Gairatovna (Modern American Journals, 2025)
This article presents a study on the effectiveness of incorporating project-research activities to enhance the specialized vocabulary acquisition of undergraduate Food Technology students. It details the methodology, intervention, and results of a quasi-experimental study, demonstrating that this active learning approach significantly improves vocabulary retention and application, addressing a critical need for domain-specific language proficiency in this field.
Keywords: Vocabulary acquisition, food technology, project-research activities, active learning, specialized terminology, ESP (English for Specific Purposes).